Entrepreneurial Passion as Mediator of the Self–Efficacy to Persistence Relationship - Cardon, Melissa S.; Kirk, Colleen P. (Entrepreneurship Theory and Practice, 2015)
What makes some entrepreneurs persist in their venture efforts while others quit? Self–efficacy has robustly been found to drive persistence, yet recent work suggests that affect, in particular entrepreneurial passion, may also enhance persistence. We empirically examine the possibility that the long–standing relationship between self–efficacy and persistence might be mediated by entrepreneurial passion. Using data from 129 entrepreneurs, we find that the self–efficacy to persistence relationship is mediated by passion for inventing and for founding but not by passion for developing firms. The passion of entrepreneurs appears to help explain the relationship between entrepreneurial self–efficacy and sustained entrepreneurial action.